PHYSICAL CHARACTERISTICS AND SENSORIC ACCEPTANCE OF JAM SHEET WITH ADDITION OF KALAMANSI ORANGE - Lydia Rahma Wati; Ika Dyah Kumalasari; Wilda Mika Sari (Jurnal Agroindustri, 2021)
Kalamansi orange jam is processed from calamansi orange fruit with the addition of papaya as a color balancer and pectin source to improve the texture of sheet jam. The aim of the research was to analyze the physical, chemical, and organoleptic properties of kalamansi orange sheet jam. Completely Randomized Design (CRD) with 1 (one) factor, namely the addition of kalamansi orange juice (10%, 20%, 30%, 40% and 50% and repeated 4 (four) times. The variables observed were physical changes, syneresis, total dissolved solids test, and shelf life. The data obtained was analyzed by the ANOVA test. The results showed that leaf jam with Calamansi orange juice had no significant effect on the overall sensory test.The best treatment in the study of kalamansi orange sheet jam was found in the addition of Kalamansi orange juice formulation F1 (10%) with a syneresis value of 0.003%; the level of damage to the kalamansi orange jam occurred on day 6 at F1 (10%), F2 (20%), F3 (30%) and F5 (50%) characterized by pale color, dry texture, hard and white grains appeared on the surface. and taste bland; total dissolved solids (TPT) of 34.6%ºbrix; and organoleptic with the panelist's preference level for kalamansi orange sheet jam of 5.64 (like slightly). Kalamansi orange has the potential to be developed into sheet jam preparations with good physical and organoleptic properties.